Analisis Pengangguran di Kelurahan Gates Nan XX Kecamatan Lubuk Begalung Kota Padang - Meza Yulia Astuti; Yulhendri Yulhendri; Menik Kurnia Siwi (Universitas Negeri Padang, 2018)
This study aims to analyze unemployment in Kelurahan Gates Nan XX Lubuk Begalung Subdistrict of Padang City which is seen from the aspect of family social status, education, income and time allocation. This research is a qualitative descriptive study. The sampling technique used is purposive sampling. Data collection techniques are observation, interview and documentation. To test the validity of data used Triangulation Technique. The results of this study indicate that unemployed are classified as half-unemployed come from families who have low economy. This can be seen from the work of parents as Fishermen, Merchants, and Daily laborers. Furthermore, many youth drop out and choose to work as fishermen, casual laborers, and fish traders in Gates Nan XX Village with an average income of Rp 50,000 per day and have 3-5 hours working hours per day. Keywords:Unemploymen